2010
DOI: 10.1371/journal.pone.0011028
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Antigen-Specific T-Cells during Clinical Tolerance Induction in Humans

Abstract: Allergen immunotherapy presents an opportunity to define mechanisms of induction of clinical tolerance in humans. Significant progress has been made in our understanding of changes in T cell responses during immunotherapy, but existing work has largely been based on functional T cell assays. HLA-peptide-tetrameric complexes allow the tracking of antigen-specific T-cell populations based on the presence of specific T-cell receptors and when combined with functional assays allow a closer assessment of the potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 75 publications
4
50
0
1
Order By: Relevance
“…Gene-expression profiling allowed the phenotypic categorization of particular CD4+ T-cell clusters, including cluster 5, which exhibited increased IL-10, CD25, and FOXP3 expression, features associated with Tregs (27,28), cluster 4, with increased IL-4 and IL-13 and low CD27, features linked to allergic Th2 cells (2), cluster 6, with low CD28 and K i -67, features linked to anergic T cells (29), cluster 3, with high CD27 and low IL-4 and IL-13 expression, features linked to nonallergic cells (2), and cluster 2, with increased IFN-γ, a feature linked to Th1 cells (30) (Fig. 2 B and C, Table 2, and Fig.…”
Section: Significancementioning
confidence: 99%
“…Gene-expression profiling allowed the phenotypic categorization of particular CD4+ T-cell clusters, including cluster 5, which exhibited increased IL-10, CD25, and FOXP3 expression, features associated with Tregs (27,28), cluster 4, with increased IL-4 and IL-13 and low CD27, features linked to allergic Th2 cells (2), cluster 6, with low CD28 and K i -67, features linked to anergic T cells (29), cluster 3, with high CD27 and low IL-4 and IL-13 expression, features linked to nonallergic cells (2), and cluster 2, with increased IFN-γ, a feature linked to Th1 cells (30) (Fig. 2 B and C, Table 2, and Fig.…”
Section: Significancementioning
confidence: 99%
“…IgG4 blocks the interaction of IgE and allergens as well as the presentation of allergen to T cells. In the late phase, after one to several months, the immune response from Th2 to Th1 is reoriented, as well as the increase in the number and function of both types of T-regulatory cells (T-reg): natural (nT-reg) and inducible (iT-reg) [107]. iT-reg originated from naive CD4 + T lymphocytes and they are the most important source of IL-10, which is an important factor in peripheral tolerance [108,109], because it inhibits IgE production from one, and on the other hand stimulates IgG4 secretion and in this way directly inhibits the activity of allergen-specific T lymphocytes (Forkhead box protein 3)) are thymus origin and exhibit synergistic effects with iT-reg cells [111] exposing high levels of IL-10 and TGF-beta [112].…”
Section: Oral Tolerancementioning
confidence: 99%
“…24,31 Both subsets, thymic selected CD4 + CD25 + Tregs and inducible Tr1 cells, seem to play together in the development of tolerance under subcutaneous and sublingual SIT: [32][33][34] Studies demonstrated an increase of CD4 + CD25 + FOXP3 + and IL-10-producing Tr1 cells in nasal and oral mucosa and in the periphery during SIT as well as an association of CD4 + CD25 + with clinical efficiency. [35][36][37][38] Hypo-proliferation of PBMCs to allergens after SIT has been mainly attributed to the induction of T-regulatory cells.…”
Section: Antigen-presenting Cellsmentioning
confidence: 99%